It’s a woman’s thing: gender roles sustaining the practice of female genital mutilation among the Kassena-Nankana of northern Ghana - Patricia Akweongo; Elizabeth F. Jackson; Shirley Appiah-Yeboah; Evelyn Sakeah; James F. Phillips (Reproductive Health, 2021)
Abstract Introduction The practice of female genital mutilation (FGM/C) in traditional African societies is grounded in traditions of patriarchy that subjugate women. It is widely assumed that approaches to eradicating the practice must therefore focus on women’s empowerment and changing gender roles. Methods This paper presents findings from a qualitative study of the FGM/C beliefs and opinions of men and women in Kassena-Nankana District of northern Ghana. Data are analyzed from 22 focus group panels of young women, young men, reproductive age women, and male social leaders. Results The social systemic influences on FGM/C decision-making are complex. Men represent exogenous sources of social influence on FGM/C decisions through their gender roles in the patriarchal system. As such, their FGM/C decision influence is more prominent for uncircumcised brides at the time of marriage than for FGM/C decisions concerning unmarried adolescents. Women in extended family compounds are relatively prominent as immediate sources of influence on FGM/C decision-making for both brides and adolescents. Circumcised women are the main source of social support for the practice, which they exercise through peer pressure in concert with co-wives. Junior wives entering a polygynous marriage or a large extended family are particularly vulnerable to this pressure. Men are less influential and more open to suggestions of eliminating the practice of FGM/C than women. Conclusion Findings attest to the need for social research on ways to involve men in the promotion of FGM/C abandonment, building on their apparent openness to social change. Investigation is also needed on ways to marshal women’s social networks for offsetting their extended family familial roles in sustaining FGM/C practices.